A Portfolio Management View Of Singapore Ageing Population - Leong, Teck Tem (2010)
Portfolio Management is defined as the art and science of making decisions about investment mix and policy, matching investments to objectives, asset allocation and balancing risk against and performance. It is used to select a portfolio of new product development projects to achieve maximize profitability or value of the portfolio, provide balance and support the strategy of the enterprise. In this dissertation, we will look into portfolio management from government, consumers and private firm views of perspective towards Singapore ageing population.